Generalist diet of Microraptor zhaoianus included mammals. Issue 2 (31st August 2022) - Hone, David W. E.; Alexander Dececchi, T.; Sullivan, Corwin; Xing, Xu; Larsson, Hans C. E.
ABSTRACT: Gut contents are extremely important for inferring trophic interactions between extinct species. These are, however, very rare in the fossil record and it is not always possible to accurately identify both the carnivore and the consumed organisms. Here we describe the remains of a small fossil mammal foot preserved inside the body cavity of the holotype specimen of the small feathered dinosaur Microraptor zhaoianus . This adds to the known diversity of diet for this genus, which also consumed birds, fish, and lizards. Previous interpretations that Microraptor was an arboreal hunter of birds and adept hunter of fish are not supported. Although the various known stomach contents would be plausible prey items based on size, there is no clear evidence that any of them were predated rather than scavenged, and Microraptor likely did both and foraged in multiple habitats.